(untitled) (Fourth World Journal, 1985)
This article critically examines the USSR’s federalist rhetoric, exposing it as a façade for a centralized Russian colonial state. Although the Soviet Union claimed to support ethnic identities under the slogan "national in form, socialist in content," real authority was concentrated in Moscow. Key ministries and the military were overwhelmingly dominated by Slavs, marginalizing minority groups like Muslims. The policy of sliyanie (cultural fusion) masked forced Russification through mass deportations (e.g., Crimean Tatars, Meskhetians), the genocide of Ukrainians during the 1932–33 famine, and the suppression of regional autonomies. Certain exceptions, such as Armenians and Georgians, were maintained for geopolitical purposes. Symbolic "rehabilitations," like that of the Crimean Tatars in 1967, perpetuated Russification rather than reversed it.